The determinants of FDI flows between the OECD and CARICOM countries - Mohan, Preeya ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Seeks to determine the factors which affect Foreign Direct Investment (FDI) flows between CARICOM and the Organization for Economic Co-operation and Development (OECD) countries.